THE THERMAL-HYDRAULICS ANALYSIS ON RADIAL AND AXIAL POWER FLUCTUATION FOR AP1000 REACTOR - Isnaini, Muhammad Darwis; Widodo, Surip; Subekti, Muhammad (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
THE THERMAL-HYDRAULICS ANALYSIS ON RADIAL AND AXIAL POWER FLUCTUATION FOR AP1000 REACTOR. The reduction of fissile material during reactor operation affects reactivity reduction. Therefore, in order to keep the reactor operating at fixed power, it must be compensated by slowly withdrawing the control-rod up. However, it will change the shape of the horizontal/axial power distribution and safety margin as well. The research carries out the calculations of the core thermal-hydraulics to determine the effect of the fluctuations of the power distribution on the thermal-hydraulic AP1000’s parameters and study their impacts on the safety margin. The calculation is done using the COBRA-EN code and the result shows that the maximum heat flux at the Beginning of Cycle (BOC) is 1624.02 kW/m2. This heat flux will then decrease by 22.75% at the Middle of Cycle (MOC) and by 0.29% at the End of Cycle (EOC). The peak fuel centerline temperature at the BOC, MOC and EOC, are 1608.15°C, 1232.15°C, and 1301.75°C, respectively. These temperature differences are caused by the heat flux effects on sub-cooled boiling regions in the cladding surface. Moreover, the value of MDNBRs at the MOC and EOC are 3.23 and 3.00, which are higher than the MDNBR at the BOC of 2.49. It could be concluded that the operating cycle of the AP1000 reactor should be operated in the MOC and the EOC, which will be more safely than be operated in the BOC.